Image-Guided Percutaneous Sclerotherapy for Orbital Low-Flow Malformation: Our Experience - Lokdarshi, Gautam; Kumar, Shwetam; Kumar, Subhash; Nitu, Nitu; Gaur, Nripen (Indian Journal of Radiology and Imaging, 2024)
For a safe sclerotherapy session to be completed in the orbital low-flow malformation (namely lymphovenous malformation or venolymphatic malformation), accurate identification of the target lesion for the drug injection is crucial. Regarding the dependability and viability of the injection approach, the authors have discussed their experiences with image-guided percutaneous sclerotherapy on a few patients.
Keywords: sclerotherapy; orbital; low-flow malformation; image-guided; LVM; fluoroscopy